Demographic and clinical characteristics of diagnosed and non‐diagnosed psychotic disorders in the community. Issue 1 (24th August 2016) - Michel, Chantal; Schimmelmann, Benno G.; Schultze‐Lutter, Frauke
Abstract: Aim: Retrospective studies of first‐episode psychosis patients have reported that psychosis often remains untreated for some time. Yet, from clinical samples, the characteristics and number of non‐diagnosed untreated psychosis patients in a community can only be estimated. Thus, this short report compares socio‐demographic and clinical features of diagnosed and non‐diagnosed psychotic individuals assessed in the community. Methods: Using telephone interviews, we clinically assessed 2682 community participants (aged 16–40 years) in the Canton of Bern, Switzerland, to examine the characteristics of non‐diagnosed psychosis. Results: Of the 41 detected psychosis patients (1.5% of the sample), 21 (54%) had already been diagnosed and treated. Non‐diagnosed individuals experienced a delusional disorder (DD) ( n  = 10) more frequently than diagnosed individuals ( n  = 1), but did not differ in other socio‐demographic characteristics. Conclusion: Further study of DD should be emphasized, along with increased awareness of the condition in primary healthcare services, as individuals with DD might present themselves for other complaints.